Cultural Memory and Trauma: Commemorating the Past in Post-Conflict Bosnia Herzegovina - Fajic, Selma (Enigma in Cultural, 2024)
Post-conflict societies grapple with the complex interplay of cultural memory and trauma. Bosnia and Herzegovina, marked by the devastating 1992-1995 war, provides a poignant case study. This research delves into how collective memory shapes commemoration practices and influences the ongoing process of healing and reconciliation. A mixed-methods approach was employed, incorporating qualitative data collection and analysis. In-depth interviews were conducted with survivors, community leaders, and cultural practitioners. Additionally, content analysis was performed on commemorative events, memorials, and public discourses. Findings highlight the dynamic nature of cultural memory. Commemoration practices serve as sites of contestation, reflecting diverse narratives and interpretations of the past. Trauma manifests in both individual and collective experiences, shaping identity and influencing social relations. In conclusion, the study underscores the crucial role of cultural memory in post-conflict societies. Commemoration serves as a vehicle for acknowledging suffering, promoting healing, and fostering reconciliation. However, it is essential to navigate the complexities of diverse narratives and ensure inclusive representation.